Health Education Using Leaflets on Medication Compliance and Prevention of Transmission in Tuberculosis Patients at Simpang Lima Gumul Hospital, Kediri - Ayu Nani Septiana; Noer Solistijaningsih (Journal of Community Health Provision, 2026)
Tuberculosis (TB) remains a major global and national public health problem requiring comprehensive management. The success of TB treatment is not only determined by the availability of medication but is also strongly influenced by patients' knowledge and adherence to therapy. This study aimed to describe the level of knowledge and adherence of TB patients after receiving health education using leaflet media at Simpang Lima Gumul Hospital, Kediri. This study employed a descriptive quantitative approach supported by qualitative data. A total of 20 respondents, consisting of TB patients and their family members, were selected using purposive sampling. Data were collected through questionnaires, observations, and in-depth interviews. Data analysis was conducted using descriptive statistics in the form of percentages. The results showed that the level of knowledge and adherence of patients was categorized as good, with an average score of 76.5%. Approximately 70–80% of respondents demonstrated improved understanding after receiving the educational intervention. Supporting factors included family support, the role of healthcare workers, and access to healthcare services, while the main barriers were treatment fatigue, drug side effects, and limited understanding of treatment duration. In conclusion, health education using leaflet media contributes to improving knowledge and adherence among TB patients.